Normal neuropsychological development in children with congenital complete heart block who may or may not be exposed to high-dose dexamethasone in utero. Issue 11 (27th February 2006) - Brucato, A; Astori, M G; Cimaz, R; Villa, P; Li Destri, M; Chimini, L; Vaccari, R; Muscarà, M; Motta, M; Tincani, A; Neri, F; Martinelli, S
Abstract : Background: Antenatal and postnatal treatment with dexamethasone (DEX) may negatively affect the neuropsychological development in children. Maternal anti-Ro/Sjögren's syndrome A (SSA) antibodies may also be associated with learning disabilities in offspring. Objective: To assess neuropsychological development in babies exposed to very high dosages of DEX in utero, whose mothers were anti-Ro/SSA positive. Methods: 13 children with congenital complete heart block (CHB) (11 exposed and 2 not exposed to DEX) and 3 healthy siblings, all of anti-Ro/SSA-positive women, were evaluated. 11 preschool-aged children (5 boys) were assessed using Griffiths Mental Development Scales. 5 school-aged children (2 boys) were examined using Wechsler Intelligence Scale for Children—Revised to check IQ and reading tests to explore the existence of learning disabilities or dyslexia. None of the children had had major neonatal complications, although those with CHB had to be paced at different intervals from birth. Results: The children had been exposed in utero to a mean total dose of 186.6 mg DEX. IQ levels were always normal (mean IQ 105.1, standard deviation (SD) 9.5). Only one child had a learning disability, of borderline clinical significance, but this child had never been exposed to DEX. Conclusion: No negative effects were found on the neuropsychological development in this cohort of children, even if they had been exposed to maternal anti-Ro/SSA antibodies and to very high dosages of DEX (much higher than those used to improve fetal lung maturity). These findings might be of interest in view of the large number of infants exposed in the past to repeated antenatal courses of steroids.